Health-related quality of life, and its determinants, among older people in rural Vietnam - Hoi Le V; Chuc Nguyen TK; Lindholm Lars (BMC, 2010)
Abstract Background The proportion of people in Vietnam aged 60 and above has increased rapidly in recent decades. However, there is a lack of evidence, particularly in rural settings, on their health-related quality of life (HRQoL) within the context of socioeconomic changes and health-sector reform in the country. This study assesses the level and determinants of HRQoL in a rural district in order to provide evidence for designing and implementing appropriate health policies. Methods In 2007, 2,873 people aged 60+ living in 2,240 households randomly selected from the FilaBavi demographic surveillance site (DSS) were interviewed using a generic EQ-5D questionnaire to assess their HRQoL. Socioeconomic characteristics of the people and their households were extracted from the DSS's re-census that year, and the EQ-5D index was calculated based on the time trade-off tariff. Multilevel-multivariate linear regression analysis was performed to measure the affect of socioeconomic factors on HRQoL. Results The EQ-5D index at old age was found to be 0.876 (95%CI: 0.870-0.882). Age between 60-69 or 70-79 years, position as household head, working until old age, literacy, and belonging to better wealth quintiles are determinants of higher HRQoL. Ageing has a primary influence on the deterioration of HRQoL at older ages, mainly due to reduction in physical rather than mental functions. Educational disparity in HRQoL is low, and exists mostly between basic and higher levels of education. Being a household head and working at old age are advantageous for attaining better quality of life in physical rather than psychological terms. Economic conditions affect HRQoL through sensory rather than physical utilities. Long-term living conditions more likely affect HRQoL than short-term economic conditions. Conclusions HRQoL at old age is at a high level, and varies substantially according to socioeconomic factors. Its determinants should be addressed in social and health policies designed to improve health of older people, especially among the most vulnerable groups.